2021
DOI: 10.26689/par.v5i1.1877
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Clinical Characteristics of 10 Cases of Asymptomatic SARS-CoV-2 Novel Coronavirus Infection

Abstract: Objective: To analyze the clinical features of asymptomatic patients infected with the SARS-CoV-2 novel coronavirus. Methods: The clinical data of 10 asymptomatic cases and 12 symptomatic cases of COVID-19 diagnosed during February 2020 to April 2020 was collected and the clinical features of the two groups of patients were compared. Results: 10 cases of asymptomatic infection and 12 cases of symptomatic patients were tested positive for the novel coronavirus nucleic acid test. There was no significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In many reports, no evidence of vertical transmission was found regarding various samples such as amniotic fluid, cord blood, neonatal throat glands, placental swabs, genital fluid, and breast milk samples in mothers infected with the virus. 13,14,[18][19][20] However, several studies exist in the literature reporting vertical transmission of SARS-CoV-2 through the placenta. [7][8][9][10] Although some show electronic microscopic changes, some have reported the presence of the SARS-CoV-2 genome in the placentas, especially in the term period.…”
Section: Discussionmentioning
confidence: 99%
“…In many reports, no evidence of vertical transmission was found regarding various samples such as amniotic fluid, cord blood, neonatal throat glands, placental swabs, genital fluid, and breast milk samples in mothers infected with the virus. 13,14,[18][19][20] However, several studies exist in the literature reporting vertical transmission of SARS-CoV-2 through the placenta. [7][8][9][10] Although some show electronic microscopic changes, some have reported the presence of the SARS-CoV-2 genome in the placentas, especially in the term period.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Data regarding the maternal immune response, vertical transmission, and placental infection have been limited largely to case reports, small case series, and systematic reviews. [8][9][10][11][12][13][14][15][16][17][18][19][20] Here, we report key biological data from a large prospective cohort study of SARS-CoV-2 infection in pregnancy regarding viral load, antibody response, transplacental antibody transfer, and placental pathology.…”
Section: Introductionmentioning
confidence: 99%
“…87 The earliest study showed that the clinical features of infected pregnant women with this virus in late pregnancy were found to be similar to those of nonpregnant patients. 80 However, since the impact of this virus on pregnant women is still limited, they should be given a consideration including their newborns, about COVID-19 management and prevention means. 89 The pregnant mother must be focused as high-risk for COVID-19 and need to lessen the contact.…”
Section: Discussionmentioning
confidence: 99%
“…79 The earliest data have reported as there is no concrete evidence for vertical transmission of SARS-CoV-2 virus because of intrauterine infections. 52,[80][81][82][83][84][85][86][87][88] It will probably be a rare that fetuses will be uninfected at the time of their birth, if intrauterine transmission of SARS-CoV-2 occur. 83 There is no information found for vertical transmission of this virus from confirmed pregnant mothers to fetuses.…”
Section: Discussionmentioning
confidence: 99%